Dysfunction of Muslim’s Public Resource: A Study of Waqf Land Disorganization in Indonesia - Sudirman Sudirman; Irwan Abdullah; Saifuddin Zuhri Qudsy; Fakhruddin Fakhruddin; Syabbul Bachri (Fakultas Syariah, 2022)
Abstract:Waqf land (donated land) is a property for people’s welfare that has not been remarkably managed in Indonesia. Poor administration and regulation of the waqf system cause dysfunction of this Muslim's most extensive resource. The waqf studies usually focus on issues around the misuse of waqf land, the swapping of waqf land, or the strategy for managing productive waqf land. Research on the disorganization of the waqf land remains unnoticed by researchers. This study complements previous writings' shortcomings by examining the patterns of waqf land disorganization and its consequences for the Muslims, including the waqf's low productivity, the waqf land position as a disputed source, and the waqf land as a lost-risk Muslim property. This study is empirical waqf research with interviews as the primary data and documents from online news website sources as the secondary data. This study indicates that the disorganization of waqf land is not only due to the absence of an administrative system and a lack of institutional commitment to waqf management. It is also rooted in Muslims' cosmological structure, who believe that waqf is the doer's afterlife savings. This belief resulted in the neglect of the waqf administration process, which led to the dysfunction of the community's resources. This study suggests further research on the contemporary waqf with its variants and waqf's practice from the doers’ and the managers' perspective to more comprehensively portray the problem of waqf land disorganization.Keywords: resource dysfunction; disorganization; waqf land; nazhir.Abstrak:Wakaf merupakan properti sumber kesejahteraan umat yang belum dikelola secara serius. Sistem administrasi dan regulasi wakaf yang buruk menyebabkan disfungsi sumber daya terbesar umat. Sejauh ini kajian wakaf terfokus pada isu sekitar penyalahgunaan tanah wakaf, tukar-guling tanah wakaf, atau strategi pengelolaan tanah wakaf produktif. Kajian seputar disorganisasi tanah wakaf masih luput dari perhatian para peneliti. Studi ini melengkapi kekurangan pelbagai tulisan terdahulu dengan mengkaji secara rinci pola disorganisasi tanah wakaf dan akibatnya bagi umat meliputi produktifitas wakaf yang masih dinilai rendah, posisi tanah wakaf sebagai sumber sengketa, dan tanah wakaf sebagai muslim property yang berisiko hilang. Kajian ini termasuk studi wakaf empiris dengan data primer dalam bentuk wawancara dan data sekunder yang diperoleh melalui dokumen dari sumber website berita online. Hasil studi ini menunjukkan bahwa disorganisasi tanah wakaf bukan hanya tidak tersedianya sistem administrasi dan rendahnya komitmen kelembagaan dalam pengelolaan wakaf, namun ternyata mengakar dalam sistem kosmologi kaum muslim yang meyakini wakaf sebagai tabungan akherat bagi wakif. Hal ini mengakibatkan pengabaian proses administrasi wakaf yang pada akhirnya menyebabkan disfungsi sumberdaya umat. Studi ini menyarankan penelitian lanjutan tentang wakaf kontemporer dengan berbagai variannya dan praktik wakaf perspektif wakif-nazhir untuk memotret problem disorganisasi tanah wakaf secara lebih komprehensif.Kata Kunci: Disfungsi sumber daya; disorganisasi; wakaf tanah; nazhir.